Central bankers in government appointed committees (2007)
I study the policy choices of members of a central bank committee, who are appointed by the government. Central bankers balance their desire to protect the Central Bank's reputation against their interest to be reappointed. Committees can be more successful than single central bankers at reducing inflation and isolating policy from government pressures. These gains are only achieved if the committee is small, and its members' turnover rate is low. The former implies high probability that a single vote affects policy, while the latter is associated with a low risk of being replaced for not supporting the government's preferred policy.